Functional systems within cryptolaundering processes: a work domain analysis model of cryptolaundering activities. Issue 2 (4th May 2021) - Desmond, Dennis; Salmon, Paul; Lacey, David
ABSTRACT: Cryptocurrencies are receiving significant attention owing to their volatility, affiliation with criminal activities and perceived role in money laundering. Traditional anti-money laundering enforcement techniques are proving ineffective due to a lack of a body of knowledge about the cryptocurrency system and the continued use of traditional approaches to disruption. This study presents a first-of-its-kind systems model of the cryptolaundering system. The authors applied Work Domain Analysis (WDA) to describe the functioning of the cryptolaundering sociotechnical system using the unique language and perspective of cryptolaunderers. The resulting WDA abstraction hierarchy demonstrates the difference between cryptolaundering and traditional money laundering efforts. Cryptolaunderers operate outside of the traditional financial system relying primarily on unregistered laundering services and employ cyber tradecraft methods while circumventing regulatory and enforcement efforts. The WDA model aided with the understanding of cryptocurrency technologies, identifies avenues for intervention in cryptolaundering activities, and provides a basis for expanding anti-cryptolaundering laws and regulations.